Simplify the following expression. (1/2x + 5/6) + (4/9x + 5/7)

1 answer

To simplify the expression \((1/2x + 5/6) + (4/9x + 5/7)\), we first combine the like terms:

  1. Combine the \(x\) terms: \[ \frac{1}{2}x + \frac{4}{9}x \]

    To add these fractions, we need a common denominator. The least common multiple of 2 and 9 is 18.

    Rewrite \(\frac{1}{2}x\) and \(\frac{4}{9}x\) with a denominator of 18: \[ \frac{1}{2}x = \frac{1 \cdot 9}{2 \cdot 9}x = \frac{9}{18}x \] \[ \frac{4}{9}x = \frac{4 \cdot 2}{9 \cdot 2}x = \frac{8}{18}x \]

    Now, add them together: \[ \frac{9}{18}x + \frac{8}{18}x = \frac{9 + 8}{18}x = \frac{17}{18}x \]

  2. Next, combine the constant terms: \[ \frac{5}{6} + \frac{5}{7} \]

    Again, we need a common denominator, which is 42.

    Rewrite \(\frac{5}{6}\) and \(\frac{5}{7}\) with a denominator of 42: \[ \frac{5}{6} = \frac{5 \cdot 7}{6 \cdot 7} = \frac{35}{42} \] \[ \frac{5}{7} = \frac{5 \cdot 6}{7 \cdot 6} = \frac{30}{42} \]

    Now, add them together: \[ \frac{35}{42} + \frac{30}{42} = \frac{35 + 30}{42} = \frac{65}{42} \]

Putting it all together, the simplified expression is: \[ \frac{17}{18}x + \frac{65}{42} \]

Thus, the final answer is: \[ \frac{17}{18}x + \frac{65}{42} \]